THE INFLUENCE OF ACCOUNTABILITY, TRANSPARENCY, AND COMPLIANCE IN VILLAGE FUND MANAGEMENT REGULATIONS ON THE PERFORMANCE OF THE NEIGHBORHOOD EMPOWERMENT INSTITUTION (LPMK) IN BENGKULU CITY - Fathiar Rizki Andiga; Nila Aprilia (Jurnal Ekonomi, 2023)
Research on the impact of accountability, transparency, and policy compliance on the performance of Neighborhood Consultative Bodies (LPMK) in Bengkulu City is limited. This study employs a quantitative census approach using questionnaires for data collection and SPSS software for analysis. Results confirm the validity of the research instruments. Findings reveal that while accountability and transparency affect LPMK performance, policy compliance does not.